P71 The Relationship between the Leicester Cough Questionnaire, Eosinophilic Airway inflammation and Asthma Patient Related Outcome Measures in Severe Asthma. (12th November 2015) - Siddiqui, S; Free, R; Bradding, P; McGarvey, L
Abstract : Background: Severe asthma is characterised by a variety of symptoms which include chronic cough, although the mechanisms responsible are poorly understood. Modulation of cough reflex sensitivity by eosinophilic airway inflammation is considered likely but has not been well studied. Likewise the impact of chronic cough on patients health status is not well known as existing asthma patient related outcome instruments such as the Juniper Asthma Control Score (ACQ-6), Asthma Quality of Life Questionnaire (AQLQ) were not primarily designed to capture cough and its related morbidity in asthma. We sought to evaluate (i) the Leicester Cough Questionnaire (LCQ) in a severe asthma population, (ii) the relationship between the Leicester Cough Questionnaire (LCQ) and the ACQ-6, AQLQ and (iii) airway inflammation in sputum in severe asthma patients. Methods: 312 patients [mean (SD) age of 60.4(16.2) years, median (IQR) GINA treatment score 5[4–5] and median (IQR) sputum eosinophil percentage of 3.0(0.5–16.6)] attending the Leicester difficult asthma service were evaluated with the LCQ, ACQ-6 and AQLQ at a single clinical visit. Induced sputum samples were also acquired at the same visit for differential cell count. Results: The LCQ demonstrated the following distribution properties: mean 15.30, standard deviation 4.49, range 4.04–21 and 10 th percentile point of 8.52. Domain specific scores were LCQ (physical) 4.8(1.45), LCQ (psychological) 5.30 (1.55) and LCQ (social) 5.19(1.67). There were modest correlations between LCQ and ACQ-6 (r = -0.60; p < 0.001) but not with AQLQ (r = -0.067). There was no correlation between LCQ and sputum eosinophilis/neutrophils. Discussion: Severe asthma is associated with a high degree of cough related morbidity that appears to be independent of eosinophilic airway inflammation and not captured fully by available patient reported outcome instruments. Further research is required to determine the validity of the LCQ and its responsiveness in severe asthma populations.